TEACHERS’ INTERCULTURAL COMPETENCE AND TEACHER EDUCATION – A CASE OF POLAND - Pajak-Wazna, Ewa (European Scientific Journal, ESJ, 2013)
While speaking of getting the young generation ready for active participation in a global society, the competence of teachers and their activities cannot be passed over. The intercultural competent teacher is able to understand, evaluate and relate to ambiguous and uncertain intercultural situations, realizing the relative validity of the own frame of reference and able to select and use communication styles and behavior that fit a specific local and intercultural context. The level of intercultural competence of teachers, their activity or passivity in the broadly understood area of culture, have an undeniable impact on students’ attitudes towards multicultural issues. Equipping teacher candidates with essential intercultural competence during the period of university studies is a precondition of rising to constantly changing new challenges of the contemporary world. In the article the realities and opportunities of forming the intercultural competence of Polish teachers are being discussed. Polish teachers and teacher candidates may acquire skills and competences necessary for satisfactory functioning in a multicultural society through university programs or in-service trainings organized mostly by NGOs.